A hollow nanofiltration membrane and its preparation method and application

By combining modified carboxymethylcellulose and pretreated β-cyclodextrin, a hollow nanofiltration membrane with excellent hydrophilicity and permeability flux was prepared, solving the problems of low retention rate and poor stability in the prior art. , efficient retention of inorganic salts and long-term thermal stability are achieved.

CN118649558BActive Publication Date: 2024-12-27SHUANGJIE HIGH TECH DEV JILIN CITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411139257.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2024-12-27
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

The existing hollow nanofiltration membranes have problems in low retention rate, poor permeability and poor stability, and it is difficult to meet the needs of drinking water treatment.

Method used

By modifying carboxymethylcellulose and pretreated β-cyclodextrin as raw materials, hollow nanofiltration membranes were prepared by phase conversion method to improve their hydrophilicity, permeability and retention properties, and the membranes were improved through modification treatment. Thermal stability.

Benefits of technology

The prepared hollow nanofiltration membrane has excellent hydrophilicity, permeability flux and long-term thermal stability, showing selective retention properties for different inorganic salts, especially the retention rate of Na2SO4 remains stable under high pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118649558B_ABST
    Figure CN118649558B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a polymer membrane, and in particular to a hollow nanofiltration membrane and a preparation method and application thereof. The preparation method of the hollow nanofiltration membrane comprises the following steps: (1) adding carboxymethyl cellulose, nano-hydroxyapatite and tartaric acid to solvent A, and performing a reflux reaction to obtain modified carboxymethyl cellulose; (2) adding polyethersulfone, polyethylene glycol and modified carboxymethyl cellulose to solvent B to obtain a casting solution; (3) using the casting solution to obtain a hollow base membrane by a phase inversion method; (4) adding β-cyclodextrin and epichlorohydrin to an aqueous solution of sodium hydroxide, stirring the reaction, and obtaining pretreated β-cyclodextrin; (5) adding the pretreated β-cyclodextrin and octadecylamine to deionized water to obtain a membrane dipping solution, heating the hollow base membrane, and rinsing with deionized water to obtain a hollow nanofiltration membrane. The hollow nanofiltration membrane has excellent permeation flux, retention and long-term thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a polymer membrane, and in particular to a hollow nanofiltration membrane and a preparation method and application thereof. Background Art

[0002] Nanofiltration membrane is a new type of pressure-driven membrane separation technology that appeared in the late 1970s. It has the following advantages: first, it has a large specific surface area, so it can be closely arranged in the membrane assembly, thereby improving the space utilization rate of the membrane assembly; second, it is self-supporting and does not require an additional support, thereby reducing production costs; third, the membrane resistance is small, it is not easy to clog, and it can operate stably for a long time; fourth, it is easy to maintain. Therefore, it has received widespread attention from researchers and has developed rapidly. At present, nanofiltration membranes have been widely used in food, water resources, environmental protection and other fields.

[0003] The safety of drinking water is directly related to the health of the general public. Water contains a large amount of organic matter and particulate pollutants, and needs to pass through a nanofiltration membrane to reduce its ionic strength, remove hardness and organic matter and particulate pollutants to meet drinking water standards. At present, there are many types of hollow nanofiltration membranes. For example, Chinese patent CN115518528A discloses a carboxymethyl cellulose nanofiltration membrane, but it has problems of low retention rate and poor permeability. Chinese patent CN109126463A discloses a method for preparing a high-flux nanofiltration membrane containing a microporous intermediate layer, which involves using β-cyclodextrin to prepare a dispersion and cover it on a base membrane to finally prepare a nanofiltration membrane, but the nanofiltration membrane has a poor stability problem. Based on this, it is necessary to further explore the preparation method of the nanofiltration membrane to improve the performance of the nanofiltration membrane. Summary of the invention

[0004] The first object of the present invention is to provide a method for preparing a hollow nanofiltration membrane, which has simple steps.

[0005] A second object of the present invention is to provide a hollow nanofiltration membrane having excellent hydrophilicity, permeation flux, retention and long-term thermal stability.

[0006] The third object of the present invention is to provide an application of a hollow nanofiltration membrane.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing a hollow nanofiltration membrane comprises the following steps:

[0009] (1) Preparation of modified carboxymethyl cellulose: carboxymethyl cellulose, nano-hydroxyapatite and tartaric acid are added to solvent A for reflux reaction. After the reaction is completed, the reaction solution is centrifuged to obtain modified carboxymethyl cellulose;

[0010] (2) preparing a casting solution: adding polyethersulfone, polyethylene glycol and modified carboxymethyl cellulose to solvent B, mixing well, and degassing to obtain a casting solution;

[0011] (3) preparing a hollow base membrane: using the casting solution obtained in step (2) to prepare a hollow base membrane by a phase inversion method;

[0012] (4) Pre-treating β-cyclodextrin: adding β-cyclodextrin and epichlorohydrin to an aqueous solution of sodium hydroxide, stirring and reacting, and obtaining pre-treated β-cyclodextrin;

[0013] (5) Preparation of hollow nanofiltration membrane: Add the β-cyclodextrin and octadecylamine pretreated in step (4) into deionized water to obtain a membrane dipping solution, heat the solution and immerse the hollow base membrane obtained in step (3) into the solution, and rinse with deionized water to obtain a hollow nanofiltration membrane.

[0014] Furthermore, in step (1), the mass ratio of carboxymethyl cellulose, nano-hydroxyapatite and tartaric acid is 1:0.3-0.6:1-2.

[0015] Furthermore, in step (1), the solvent A is an ethanol aqueous solution, the mass concentration of ethanol in the ethanol aqueous solution is 45-55%, and the reflux reaction time is 4-5h.

[0016] Furthermore, in step (4), the mass ratio of sodium hydroxide, β-cyclodextrin and epichlorohydrin is 1:900-1000:200-300, the concentration of the sodium hydroxide aqueous solution is 0.10-0.15 mol / L, the temperature of the stirring reaction is 35-45° C., and the time is 2-3 h.

[0017] Furthermore, in step (2), the mass concentration of the polyethersulfone is 15-18%, the mass concentration of the polyethylene glycol is 2-4%, the mass concentration of the modified carboxymethyl cellulose is 0.1-0.2%, and the polyethylene glycol is one of polyethylene glycol 400, polyethylene glycol 600, polyethylene glycol 800, and polyethylene glycol 1000.

[0018] Furthermore, in step (2), the solvent B is DMF, and the degassing time is 4-7 hours.

[0019] Furthermore, the phase transformation method in step (3) comprises the following steps: under constant temperature and pressure conditions, the casting solution is passed through a spinning nozzle, a coagulation bath, a cleaning bath, and a filament drawing process to obtain a primary membrane; and then the primary membrane is coagulated into a membrane, soaked, and dried in the shade.

[0020] Furthermore, in step (5), the mass ratio of the pretreated β-cyclodextrin to octadecylamine is 1:0.2-0.5, the concentration of β-cyclodextrin in the dipping solution is 0.5-1.0 g / L; the temperature after heating is 40-45° C., and the immersion time is 1-2 h.

[0021] A hollow nanofiltration membrane is prepared by using the hollow nanofiltration membrane preparation method.

[0022] The application of the hollow nanofiltration membrane is to use the hollow nanofiltration membrane for the treatment of direct drinking water.

[0023] The beneficial technical effects of the present invention are:

[0024] The present invention modifies carboxymethyl cellulose to improve its dispersibility, stability and hydrophilicity. β-cyclodextrin is pretreated to improve its swelling performance and hydrophilicity. The present invention uses modified carboxymethyl cellulose, pretreated β-cyclodextrin and the like as raw materials to prepare a hollow nanofiltration membrane. The electron microscope image shows that the hollow nanofiltration membrane has a mesh structure and a uniform pore size distribution, so that the membrane surface has a strong water storage capacity. The performance of the hollow nanofiltration membrane was further tested, and the results showed that: (1) The addition of pretreated β-cyclodextrin and modified carboxymethyl cellulose improves the hydrophilicity of the hollow nanofiltration membrane, thereby increasing the water flux of the hollow nanofiltration membrane. (2) The hollow nanofiltration membrane of the present invention is a negatively charged nanofiltration membrane, which shows a certain selectivity in the retention performance of different inorganic salts, and the retention performance is R (Na 2 SO 4 )>R(MgSO 4 )>R(MgCl 2 )>R(NaCl). (3) The hollow nanofiltration membrane of the present invention was operated at a pressure of 5 bar for 84 hours to remove Na 2 SO 4 There is no significant change in the retention rate, which means that it has excellent long-term thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is an electron microscopy analysis diagram of the hollow nanofiltration membrane prepared in Example 1 of the present invention;

[0026] Figure 2 This is an electron microscope analysis diagram of the hollow nanofiltration membrane prepared in Comparative Example 1 of the present invention;

[0027] Figure 3 This is an electron microscopy analysis diagram of the hollow nanofiltration membrane prepared in Comparative Example 4 of the present invention;

[0028] Figure 4 It is a graph showing the water flux results of the hollow nanofiltration membranes prepared in Example 1 and Comparative Examples 1-4 of the present invention;

[0029] Figure 5 It is a graph showing the rejection rate results of the hollow nanofiltration membranes prepared in Example 1 and Comparative Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0030] The following is a further detailed description of the present invention in conjunction with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, several simple deductions or replacements can also be made, all of which should be deemed to belong to the protection scope of the present invention. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0031] Example

[0032] Example 1

[0033] This embodiment provides a method for preparing a hollow nanofiltration membrane, which is as follows:

[0034] (1) Preparation of modified carboxymethyl cellulose

[0035] According to the mass ratio of carboxymethyl cellulose, nano-hydroxyapatite and tartaric acid of 1:0.4:1, carboxymethyl cellulose, nano-hydroxyapatite and tartaric acid were added to an ethanol aqueous solution, the mass concentration of ethanol in the ethanol aqueous solution was 50%, and the reaction was refluxed for 4.5 hours. After the reaction was completed, the reaction solution was cooled to room temperature and centrifuged to remove water and ethanol. After the centrifugation, the solid phase was collected and washed with water and dried to obtain modified carboxymethyl cellulose.

[0036] (2) Preparation of casting solution

[0037] Add polyethersulfone, polyethylene glycol 400 and modified carboxymethyl cellulose into DMF and mix evenly, wherein the mass concentration of polyethersulfone is 16%, the mass concentration of polyethylene glycol 400 is 3%, and the mass concentration of modified carboxymethyl cellulose is 0.15%. Degassing is performed for 6 hours to obtain a casting solution.

[0038] (3) Preparation of hollow base membrane

[0039] Under the conditions of constant temperature and pressure of 70°C and 0.1MPa, the casting solution obtained in step (2) is passed through a spinning nozzle, a coagulation bath, and a cleaning bath, and is arranged on a wire arrangement tube to form a primary membrane; then, the membrane is placed in deionized water at room temperature to coagulate into a membrane, and soaked for 36 hours. During the soaking process, the deionized water is replaced every 12 hours. After being taken out, the membrane is naturally dried in the shade at room temperature using a membrane pressing plate to obtain a hollow base membrane.

[0040] (4) Pretreatment of β-cyclodextrin

[0041] Calculated by the amount of sodium hydroxide, β-cyclodextrin and epichlorohydrin are added to a 0.15 mol / L aqueous solution of sodium hydroxide at a mass ratio of 1:950:270, and the mixture is stirred and reacted at 40°C for 2.6 hours. The material is discharged, washed to neutrality, and dried to obtain pretreated β-cyclodextrin.

[0042] (5) Preparation of hollow nanofiltration membrane

[0043] According to the mass ratio of the pretreated β-cyclodextrin to octadecylamine of 1:0.4, the β-cyclodextrin and octadecylamine pretreated in step (4) are added to deionized water to obtain a membrane dipping solution, wherein the concentration of β-cyclodextrin in the membrane dipping solution is 0.5 g / L; after heating to 42°C, the hollow base membrane obtained in step (3) is immersed therein for 1 hour, and then rinsed with deionized water to obtain a hollow nanofiltration membrane.

[0044] This embodiment also provides a hollow nanofiltration membrane, which is prepared using the above-mentioned method for preparing the hollow nanofiltration membrane.

[0045] Example 2

[0046] This embodiment provides a method for preparing a hollow nanofiltration membrane, which is as follows:

[0047] (1) Preparation of modified carboxymethyl cellulose

[0048] According to the mass ratio of carboxymethyl cellulose, nano-hydroxyapatite and tartaric acid of 1:0.3:1.5, carboxymethyl cellulose, nano-hydroxyapatite and tartaric acid were added to an ethanol aqueous solution, the mass concentration of ethanol in the ethanol aqueous solution was 55wt%, and the reaction was refluxed for 5h. After the reaction was completed, the reaction solution was cooled to room temperature and centrifuged to remove water and ethanol. After the centrifugation, the solid phase was collected and washed with water and dried to obtain modified carboxymethyl cellulose.

[0049] (2) Preparation of casting solution

[0050] Add polyethersulfone, polyethylene glycol 600 and modified carboxymethyl cellulose into DMF and mix evenly, wherein the mass concentration of polyethersulfone is 15%, the mass concentration of polyethylene glycol 600 is 2%, and the mass concentration of modified carboxymethyl cellulose is 0.2%. Degassing is performed for 7 hours to obtain a casting solution.

[0051] (3) Preparation of hollow base membrane

[0052] Under the conditions of constant temperature and pressure of 70°C and 0.1MPa, the casting solution obtained in step (2) is passed through a spinning nozzle, a coagulation bath, and a cleaning bath, and is arranged on a wire arrangement tube to form a primary membrane; then, the membrane is placed in deionized water at room temperature to coagulate into a membrane, and soaked for 36 hours. The deionized water is replaced every 12 hours during the soaking process. After being taken out, the membrane is naturally dried in the shade at room temperature using a membrane pressing plate to obtain a hollow base membrane.

[0053] (4) Pretreatment of β-cyclodextrin

[0054] Calculated by the amount of sodium hydroxide, β-cyclodextrin and epichlorohydrin are added to a 0.10 mol / L aqueous solution of sodium hydroxide at a mass ratio of 1:1000:300, and the mixture is stirred and reacted at 35°C for 3 hours. The material is discharged, washed to neutrality, and dried to obtain pretreated β-cyclodextrin.

[0055] (5) Preparation of hollow nanofiltration membrane

[0056] According to the mass ratio of the pretreated β-cyclodextrin to octadecylamine of 1:0.5, the β-cyclodextrin and octadecylamine pretreated in step (4) are added to deionized water to obtain a membrane dipping solution, wherein the concentration of β-cyclodextrin in the membrane dipping solution is 0.8 g / L; after heating to 40° C., the hollow base membrane obtained in step (3) is immersed in it for 1.5 hours, and rinsed with deionized water to obtain a hollow nanofiltration membrane.

[0057] This embodiment also provides a hollow nanofiltration membrane, which is prepared using the above-mentioned method for preparing the hollow nanofiltration membrane.

[0058] Example 3

[0059] This embodiment provides a method for preparing a hollow nanofiltration membrane, which is as follows:

[0060] (1) Preparation of modified carboxymethyl cellulose

[0061] According to the mass ratio of carboxymethyl cellulose, nano-hydroxyapatite and tartaric acid of 1:0.6:2, carboxymethyl cellulose, nano-hydroxyapatite and tartaric acid were added to an ethanol aqueous solution, the mass concentration of ethanol in the ethanol aqueous solution was 45%, and the reaction was refluxed for 4 hours. After the reaction was completed, the reaction solution was cooled to room temperature and centrifuged to remove water and ethanol. After the centrifugation, the solid phase was collected and washed with water and dried to obtain modified carboxymethyl cellulose.

[0062] (2) Preparation of casting solution

[0063] Add polyethersulfone, polyethylene glycol 800 and modified carboxymethyl cellulose into DMF and mix evenly, wherein the mass concentration of polyethersulfone is 18%, the mass concentration of polyethylene glycol 800 is 4%, and the mass concentration of modified carboxymethyl cellulose is 0.1%. Degassing is carried out for 4 hours to obtain a casting solution.

[0064] (3) Preparation of hollow base membrane

[0065] Under the conditions of constant temperature and pressure of 70°C and 0.1MPa, the casting solution obtained in step (2) is passed through a spinning nozzle, a coagulation bath, and a cleaning bath, and is arranged on a wire arrangement tube to form a primary membrane; then, the membrane is placed in deionized water at room temperature to coagulate into a membrane, and soaked for 36 hours. The deionized water is replaced every 12 hours during the soaking process. After being taken out, the membrane is naturally dried in the shade at room temperature using a membrane pressing plate to obtain a hollow base membrane.

[0066] (4) Pretreatment of β-cyclodextrin

[0067] Calculated by the amount of sodium hydroxide, β-cyclodextrin and epichlorohydrin are added to a 0.12 mol / L aqueous solution of sodium hydroxide at a mass ratio of 1:900:200, and the mixture is stirred and reacted at 45°C for 2 hours. The mixture is discharged, washed to neutrality, and dried to obtain pretreated β-cyclodextrin.

[0068] (5) Preparation of hollow nanofiltration membrane

[0069] According to the mass ratio of the pretreated β-cyclodextrin to octadecylamine of 1:0.2, the β-cyclodextrin and octadecylamine pretreated in step (4) are added to deionized water to obtain a membrane dipping solution, wherein the concentration of β-cyclodextrin in the membrane dipping solution is 1.0 g / L; after heating to 45° C., the hollow base membrane obtained in step (3) is immersed in it for 2 hours, and rinsed with deionized water to obtain a hollow nanofiltration membrane.

[0070] This embodiment also provides a hollow nanofiltration membrane, which is prepared using the above-mentioned method for preparing the hollow nanofiltration membrane.

[0071] Comparative Example

[0072] Comparative Example 1

[0073] This comparative example provides a method for preparing a hollow nanofiltration membrane, which is different from Example 1 in that:

[0074] Omit step (1);

[0075] (2) Preparation of casting solution

[0076] Polyethersulfone, polyethylene glycol 400 and carboxymethyl cellulose were added to DMF and mixed evenly, wherein the mass concentration of polyethersulfone was 16%, the mass concentration of polyethylene glycol 400 was 3%, and the mass concentration of carboxymethyl cellulose was 0.15%, and degassed for 6 hours to obtain a casting solution. The rest was the same as in Example 1.

[0077] Comparative Example 2

[0078] This comparative example provides a method for preparing a hollow nanofiltration membrane, which is different from Example 1 in that:

[0079] Omit step (1);

[0080] (2) Preparation of casting solution

[0081] Polyethersulfone, polyethylene glycol 400, carboxymethyl cellulose and nano-hydroxyapatite were added to DMF and mixed evenly, wherein the mass concentration of polyethersulfone was 16%, the mass concentration of polyethylene glycol 400 was 3%, the mass concentration of carboxymethyl cellulose was 0.11%, and the mass concentration of nano-hydroxyapatite was 0.04%, and degassed for 6 hours to obtain a casting solution. The rest was the same as in Example 1.

[0082] Comparative Example 3

[0083] This comparative example provides a method for preparing a hollow nanofiltration membrane, which is different from Example 1 in that:

[0084] Omit step (1);

[0085] (2) Preparation of casting solution

[0086] Polyethersulfone, polyethylene glycol 400, nano-hydroxyapatite and tartaric acid were added to DMF and mixed evenly, wherein the mass concentration of polyethersulfone was 16%, the mass concentration of polyethylene glycol 400 was 3%, the mass concentration of nano-hydroxyapatite was 0.10%, and the mass concentration of tartaric acid was 0.05%, and degassed for 6 hours to obtain a casting solution. The rest was the same as in Example 1.

[0087] Comparative Example 4

[0088] This comparative example provides a method for preparing a hollow nanofiltration membrane, which is different from Example 1 in that:

[0089] Omit step (4);

[0090] (5) Preparation of hollow nanofiltration membrane

[0091] According to the mass ratio of β-cyclodextrin to octadecylamine of 1:0.4, β-cyclodextrin and octadecylamine were added to deionized water to obtain a membrane dipping solution, which was heated to 37° C. and then immersed in the hollow base membrane, and rinsed with deionized water to obtain a hollow nanofiltration membrane. The rest was the same as in Example 1.

[0092] Test example

[0093] Test Example 1

[0094] In this test example, the hollow nanofiltration membranes prepared in Example 1, Comparative Example 1 and Comparative Example 4 were analyzed by scanning electron microscope. The results are as follows: Figure 1-3 shown.

[0095] Figure 1 This is an electron microscope analysis diagram of the hollow nanofiltration membrane prepared in Example 1 of the present invention. Figure 2 This is an electron microscope analysis diagram of the hollow nanofiltration membrane prepared in Comparative Example 1 of the present invention. Figure 3This is an electron microscope analysis of the hollow nanofiltration membrane obtained in Comparative Example 4 of the present invention. Figure 1-3 It can be seen that compared with Comparative Example 1 and Comparative Example 4, the pore size distribution and thickness of the hollow nanofiltration membrane prepared by the present invention are more uniform.

[0096] Test Example 2

[0097] This test example tests the performance of the hollow nanofiltration membranes prepared in Example 1 and Comparative Examples 1-4, and the test method is as follows:

[0098] (1) Permeation flux

[0099] At room temperature and 10 bar pressure, the hollow nanofiltration membranes prepared in Example 1 and Comparative Examples 1-4 were pre-pressed with pure water for 30 minutes to achieve a stable flux, and then tested at 5 bar pressure. The effective area of ​​the hollow nanofiltration membranes prepared in Example 1 and Comparative Examples 1-4 was 40×10 -4 m 2 , the permeation flux P of each hollow nanofiltration membrane is calculated by passing pure water, and the calculation formula is as follows:

[0100] P = V / (A × t × Δp), V represents the permeation volume, m 3 ; A represents the effective area of ​​the membrane, m 2 ; t is the filtration time, s; Δp is the osmotic pressure, bar. Figure 4 shown.

[0101] Figure 4 The water flux results of the hollow nanofiltration membranes prepared in Example 1 and Comparative Examples 1-4 of the present invention are shown in FIG. Figure 4 It can be seen that the hollow nanofiltration membrane of the present invention has excellent permeation flux. Further analysis shows that the addition of pretreated β-cyclodextrin and modified carboxymethyl cellulose improves the hydrophilicity of the hollow nanofiltration membrane, thereby increasing the water flux of the hollow nanofiltration membrane.

[0102] (2) Retention rate

[0103] At room temperature and 10 bar pressure, the hollow nanofiltration membranes prepared in Example 1 and Comparative Examples 1-4 were pre-pressed with pure water for 30 minutes to achieve a stable flux, and then at 5 bar pressure, 250 ppm of sodium chloride, magnesium chloride, sodium sulfate, and magnesium sulfate were filtered using the hollow nanofiltration membranes prepared in Example 1 and Comparative Examples 1-4, respectively. The selective permeability of each hollow nanofiltration membrane was characterized by the removal rate of salt in the four solutions, and the retention rate of the membrane was calculated as follows:

[0104] R = [1-(K P / K R )]×100%, where K P , K RRespectively represent the conductivity of the salt solution in the permeate and the original solution. The results are shown in Figure 5 shown.

[0105] Figure 5 The figure is a result diagram of the retention rate of the hollow nanofiltration membranes prepared in Example 1 of the present invention and Comparative Examples 1-4. Figure 5 It can be seen that the retention performance of the hollow nanofiltration membrane prepared by the present invention is R (Na 2 SO 4 )>R(MgSO 4 )>R(MgCl 2 )>R(NaCl). The above results show that the hollow nanofiltration membrane of the present invention is a negatively charged nanofiltration membrane, which has a certain selectivity for the retention performance of different inorganic salts. Specifically, Na 2 SO 4 The retention rate of is the highest, and the retention rate of NaCl is relatively low.

[0106] Compared with Example 1, the retention rates of the hollow nanofiltration membranes prepared in Comparative Examples 1-4 have changed to varying degrees. Further comparative analysis shows that Comparative Examples 1-4 adjusted the use of pretreated β-cyclodextrin and modified carboxymethyl cellulose in the process of preparing the hollow nanofiltration membrane, thereby causing the retention rate of the prepared hollow nanofiltration membrane to change.

[0107] (3) Long-term thermal stability

[0108] The feed solution was heated in a water bath and maintained at 70°C. The feed solution was 250 ppm of Na 2 SO 4 The hollow nanofiltration membranes prepared in Example 1 and Comparative Examples 1-4 were pre-pressed with pure water for 30 min at a pressure of 10 bar, and then the hollow nanofiltration membranes of each group were tested for Na 2 SO 4 The results are shown in Table 1.

[0109] Table 1

[0110]

[0111] It can be seen from Table 1 that the hollow nanofiltration membrane of the present invention has a significant effect on Na after being operated for 84 hours under a pressure of 5 bar. 2 SO 4 There is no obvious change in the retention rate, that is, the hollow nanofiltration membrane of the present invention has excellent long-term thermal stability.

[0112] Compared with Example 1, the hollow nanofiltration membranes prepared in Comparative Examples 1-4 were operated at a pressure of 5 bar for 84 hours and showed a significant improvement in the Na 2 SO 4The above results show that in the process of preparing the hollow nanofiltration membrane, the use of pretreated β-cyclodextrin and modified carboxymethyl cellulose in Comparative Examples 1-4 is adjusted, which will lead to a decrease in the long-term thermal stability of the prepared hollow nanofiltration membrane.

[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.

Claims

1. A method for preparing a hollow nanofiltration membrane, characterized in that: The following steps are involved: (1) Preparation of modified carboxymethyl cellulose: carboxymethyl cellulose, nano-hydroxyapatite and tartaric acid are added to solvent A for reflux reaction. After the reaction is completed, the reaction solution is centrifuged to obtain modified carboxymethyl cellulose; (2) preparing a casting solution: adding polyethersulfone, polyethylene glycol and modified carboxymethyl cellulose to solvent B, mixing well, and degassing to obtain a casting solution; (3) preparing a hollow base membrane: using the casting solution obtained in step (2) to prepare a hollow base membrane by a phase inversion method; (4) Pre-treating β-cyclodextrin: adding β-cyclodextrin and epichlorohydrin to an aqueous solution of sodium hydroxide, stirring and reacting, and obtaining pre-treated β-cyclodextrin; (5) preparing a hollow nanofiltration membrane: adding the β-cyclodextrin and octadecylamine pretreated in step (4) to deionized water to obtain a membrane dipping solution, heating the solution and dipping the hollow base membrane obtained in step (3) into the solution, and rinsing the solution with deionized water to obtain a hollow nanofiltration membrane; Wherein, the mass ratio of carboxymethyl cellulose, nano-hydroxyapatite and tartaric acid in step (1) is 1:0.3-0.6:1-2, the solvent A is an ethanol aqueous solution, the mass concentration of ethanol in the ethanol aqueous solution is 45-55%, and the reflux reaction time is 4-5h; In step (2), the mass concentration of polyethersulfone is 15-18%, the mass concentration of polyethylene glycol is 2-4%, the mass concentration of modified carboxymethyl cellulose is 0.1-0.2%, the polyethylene glycol is one of polyethylene glycol 400, polyethylene glycol 600, polyethylene glycol 800, and polyethylene glycol 1000, the solvent B is DMF, and the degassing time is 4-7 hours; The phase conversion method in step (3) comprises the following steps: under constant temperature and pressure conditions, passing the casting solution through a spinning nozzle, a coagulation bath, a cleaning bath, and a wire drawing film to obtain a primary film; then coagulating the primary film into a film, soaking it, and drying it in the shade to obtain the film; In step (4), the mass ratio of sodium hydroxide, β-cyclodextrin and epichlorohydrin is 1:900-1000:200-300, the concentration of the sodium hydroxide aqueous solution is 0.10-0.15 mol / L, the temperature of the stirring reaction is 35-45°C, and the time is 2-3h; In step (5), the mass ratio of the pretreated β-cyclodextrin to octadecylamine is 1:0.2-0.5, the concentration of β-cyclodextrin in the membrane dipping solution is 0.5-1.0 g / L; the temperature after heating is 40-45° C., and the immersion time is 1-2 h.

2. A hollow nanofiltration membrane, characterized in that: The hollow nanofiltration membrane is prepared by the preparation method of claim 1.

3. The use of the hollow nanofiltration membrane according to claim 2, characterized in that: The hollow nanofiltration membrane is used for treating direct drinking water.